If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -6(3b + 1) = 39 + -8b Reorder the terms: -5 + -6(1 + 3b) = 39 + -8b -5 + (1 * -6 + 3b * -6) = 39 + -8b -5 + (-6 + -18b) = 39 + -8b Combine like terms: -5 + -6 = -11 -11 + -18b = 39 + -8b Solving -11 + -18b = 39 + -8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8b' to each side of the equation. -11 + -18b + 8b = 39 + -8b + 8b Combine like terms: -18b + 8b = -10b -11 + -10b = 39 + -8b + 8b Combine like terms: -8b + 8b = 0 -11 + -10b = 39 + 0 -11 + -10b = 39 Add '11' to each side of the equation. -11 + 11 + -10b = 39 + 11 Combine like terms: -11 + 11 = 0 0 + -10b = 39 + 11 -10b = 39 + 11 Combine like terms: 39 + 11 = 50 -10b = 50 Divide each side by '-10'. b = -5 Simplifying b = -5
| -5x-6(x-5)=-x+30 | | 4(w+3)=8w | | 3x-11=x^2-9 | | D^2+8*d+9=0 | | 15-3*4= | | 4x^2-5=-5x+3 | | 3x+24y=9 | | -(8-4r)=-5+4r | | 24x^2+2xy-y^2=0 | | 23+5x=-2(x+6) | | 7(1+8v)+2v=7-6v | | 6(1-2x)-5=-83 | | 24x^2+2xr-r^2=0 | | 2x^3+x^2-19x+36=y | | -[2]=x-9 | | -2(v+3)=-18 | | x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 | | 5(n+5)=34+8n | | f(x)=2x^3+x^2-19x+36 | | 3(x+2.5)=-7.5 | | x+6-2x-4=0 | | 9+3(2x-6)=14 | | -54=9n | | 6n-12=150 | | 3(x+2.5)=7.5 | | 4+2(a+4)=-20 | | 9x-6=2x+8 | | 4x+2(3x-6)=4 |